Patient-initiated questions: How can doctors encourage them and improve the consultation process? A qualitative study. Issue 10 (16th October 2013) - Murtagh, G M; Furber, L; Thomas, A L
Abstract : Objective: To investigate the circumstances under which patients initiate direct questions in oncology consultations. Design: Conversation analysis of 47 consultations between oncologists and patients with cancer. Setting: An oncology clinic at a teaching hospital in the East Midlands. Participants: 16 Oncologists and 67 cancer patients. Outcome measure: Patient initiated direct questions. Results: On the whole patients' direct questions are designed to seek specific information regarding, the cancer itself, treatment options or their experience of symptoms. When patients do ask direct questions they typically follow the announcement of test results where some reference to the details of those results, is provided. More specifically, there seems to be a relation between showing the patient their scan/X-ray results, patient involvement and patient-initiated direct questions. Higher levels of patient-initiated direct questions were clustered around occasions where doctors provided information and explanations of test results (12 consultations) sometimes with direct reference to scan or X-ray results (7 consultations). Conclusions: This study highlights the importance of careful explanation of diagnostic evidence as a factor contributing to increased patient involvement. More specifically, the findings suggest that, when appropriate, invoking diagnostic evidence (eg, scan or X-ray results) is an effective way of increasing levels of patient question asking. Doctors need to be able to encourage patient question asking to ensure that patients have at their disposal an important means through which they can determine their information needs. Although these results come from a study of oncology consultations, the findings may be transferable to other clinical contexts.